The Effect of Teaching Models and Motor Skill Levels on The Result of Basketball Learning Technique (Journal of Physical Education and Sports, 2019)
This study aimed to determine: (1) The different effects of reciprocal and inclusion teaching technique on the basketball layup shoot learning results. (2) The different effects of high and low motor skills on the basketball layup shoot learning results. (3) The relationship between teaching technique and motor skills to the basketball layup shoot learning results. This research used 2x2 factorial experiment design. The research population was 67 students of Department of Sports Coaching Education, Faculty of Sports, Universitas Negeri Semarang. The sampling technique used purposive random sampling, a sample of 40 students. The data analysis technique used was a two-way ANAVA test and a significance level of a = 0.05, and the Tukey test. The results of the research were: (1) The effect of the teaching technique and motor skills to the basketball layup shoot learning results, Fvalue = 4.367 and significant value 0.044 is smaller than significant value 0.05, (2) The effect of high and low motor ability, Fvalue = 82.010 and significant value 0.000 is smaller than significant value 0.05, (3) The relation between teaching technique and motor skills to the basketball layup shoot learning results, Fvalue = 5.239 and significant value 0.028 smaller than significant value 0.05.